Uso de habitat por escorpiões do Bioma Pampa: efeito do uso do solo e do relevo - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Many factors influence the habitat choice by scorpions, as soil properties, microclimate of shelters or hunting territories, extent and nature of vegetation, prey abundance, and the animal’s age. The objective of this study was to describe the habitat use (native grassland with livestock x Eucalyptus afforestation; upland x lowland) by the scorpion community in the Pampa biome, as well as to teste the relationship of environmental variables with the scorpion abundance. We recorded 608 scorpions: 528 individuals from Tityus uruguayensis, and 80 from Bothriurus bonariensis. Both species were found in all areas searched, and they co-occurred in transects of all areas using all habitat sampled. However, T. uruguayensis was especially abundant in the transects of upland in Eucalyptus croplands, while B. bonariensis was more abundant in uplands from native grasslands with livestock, presenting low occurrence in Eucalyptus afforestation. Our results show the importance of preserving the Pampa biome to maintain the structure of scorpion assemblage conserved, since Eucalyptus afforestations were not a habitat successfully used by Bothriurus bonariensis and favored the occurrence of Tityus uruguayensis, allowing them to reach very high abundance, which may cause several environmental imbalances.
Keywords: Bothriurus bonariensis; Campo nativo; Tityus uruguayensis; Cultivo de Eucalyptus; Eucalyptus afforestation; Native grasslands; CNPQ::CIENCIAS BIOLOGICAS